The Efficacy of Using SCB Guidelines to Facilitate Conservation Science-Faith Collaboration: Experiences in the Field - Schaefer, Jame; Magellan, Kit; Sluka, Robert; Kolipaka, Shekhar; Gonzalez, Oscar; Razali, Akmal Arif Mohd; Clements, Gopalasamy Reuben; Elkin, Chantal (Frontiers in Environmental Science, 2020)
Recognizing the need to identify ways in which conservation researchers and practitioners can work constructively with faith leaders and communities to conserve biological diversity, the Religion and Conservation Biology Working Group of the Society for Conservation Biology formally launched the Best Practices Project in March 2016 for the purpose of collecting recommendations from SCB members throughout the world. A survey of members in 2016, a forum at the 2016 International Marine Conservation Congress in Newfoundland/Labrador, a symposium, workshop and poster session at the 2017 International Congress for Conservation Biology in Colombia, and an e-mail request to RCBWG members in October 2017 yielded many recommendations that constitute Guidelines for Interacting with Faith-based Leaders and Communities: A Proposal by and for Members of the Society for Conservation Biology published by the SCB in May 2018. Members have been reporting the efficacy of following these guidelines in their projects, and five who worked with different faiths presented their experiences in the field during a symposium at the 2019 ICCB in Malaysia. Abridged versions of their presentations are shared in this article with focus on guidelines that proved most helpful for facilitating conservation-faith collaboration to achieve project goals. Discussed subsequently are ways in which conservationists and faith communities benefited from their joint efforts, reasons why conservationists should consider engaging faith communities in their projects, and impediments to collaboration that must be overcome. The SCB guidelines are listed succinctly, and conservationists are urged to consider using them in their projects.